Design and application of a device for wiping and disinfecting the suspended ultraviolet lamp (一种悬吊式紫外线灯管消毒擦拭装置的研制及应用) - WEN Qingzhi (温庆芝); LIU Yugeng (刘禹赓); GAO Xuejun (高学军); WANG Qiang (王强); GAO Yan (高燕); JIA Ran (贾然) (Journal of International Translational Medicine Limited, 2022)
This paper introduced the design and application of a device for wiping and disinfecting the suspended uncovered ultraviolet lamp. This device had advantages of low cost, easy-to-operate and high security and sound disinfection effect, could reduce labor cost, reduce material consumption and eliminate hidden dangers of personal safety, and meet the requirements of hospital infection prevention and control. (本研究介绍一款新型无罩悬吊紫外线灯管擦拭装置, 其制作成本低、操作方便、安全性高, 消毒效果优良, 不仅提高了感染科悬吊式紫外线灯管消毒擦拭工作效率, 减少人力成本和物资消耗, 且避免了不必要的安全隐患, 符合院内感染防控要求。)